2022
DOI: 10.1002/anie.202210568
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear Nanoribbons for Selective Killing of Osteosarcoma Cells

Abstract: Herein, we show intranuclear nanoribbons formed upon dephosphorylation of leucine-rich L-or Dphosphopeptide catalyzed by alkaline phosphatase (ALP) to selectively kill osteosarcoma cells. Being dephosphorylated by ALP, the peptides are first transformed into micelles and then converted into nanoribbons. The peptides/assemblies first aggregate on cell membranes, then enter cells via endocytosis, and finally accumulate in nuclei (mainly in nucleoli). Proteomics analysis suggests that the assemblies interact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 65 publications
2
35
0
Order By: Relevance
“…ALP is an essential enzyme overexpressed on cancer cell membranes or oversecreted by cancer cells. , Previous reports have illustrated the potential applications of ALP-triggered assemblies of polymers or nanoparticles toward tumor-specific recognition and antitumor therapy. Therefore, the PEY P -Cy5 nano-switch (DP = 146, Tyr content = 25 mol %) could serve as a promising detector to differentiate tumor cells from normal cells based on the ALP-induced fluorescence “turn on”. Herein, three tumor cell lines (HeLa, HepG2, and 4T1 cells) with high ALP levels and two noncancerous cell lines (H9C2 and 3T3) with minimal ALP levels were adopted (Figure S16).…”
Section: Resultsmentioning
confidence: 97%
“…ALP is an essential enzyme overexpressed on cancer cell membranes or oversecreted by cancer cells. , Previous reports have illustrated the potential applications of ALP-triggered assemblies of polymers or nanoparticles toward tumor-specific recognition and antitumor therapy. Therefore, the PEY P -Cy5 nano-switch (DP = 146, Tyr content = 25 mol %) could serve as a promising detector to differentiate tumor cells from normal cells based on the ALP-induced fluorescence “turn on”. Herein, three tumor cell lines (HeLa, HepG2, and 4T1 cells) with high ALP levels and two noncancerous cell lines (H9C2 and 3T3) with minimal ALP levels were adopted (Figure S16).…”
Section: Resultsmentioning
confidence: 97%
“…El-Sayed et al [ 232 ] showed that AuNPs modified with NLS peptides targeted the nucleus and caused DNA damage and cell cycle arrest. Meanwhile, nanoribbons formed upon dephosphorylation of leucine-rich L-or D-phosphopeptide (1Lp and 1Dp) catalyzed by ALP also has nucleus targeting, the repeated stimulation of the OS cells by the peptides sensitizes the tumor cells rather than inducing resistance [ 233 ] (Fig. 9 f).…”
Section: Active Targetingmentioning
confidence: 99%
“…Replacing the L-amino acid residues by the corresponding D-amino acid residues produces a D-peptide EISA substrate (66). [58] Upon the dephosphorylation catalyzed by ALP, 66 turns into 67 to form intranuclear nanoribbons in osteosarcoma cells, such as Saos2 and SJSA1. The preliminary mechanistic investigation [58] indicates that partial dephosphorylation of 66 results in micelles, which enter cells via endocytosis to interact with histone proteins, then form nanoribbons of 67 inside nuclei of Saos2 cells.…”
Section: Eisa Of Peptidesmentioning
confidence: 99%
“…[58] Upon the dephosphorylation catalyzed by ALP, 66 turns into 67 to form intranuclear nanoribbons in osteosarcoma cells, such as Saos2 and SJSA1. The preliminary mechanistic investigation [58] indicates that partial dephosphorylation of 66 results in micelles, which enter cells via endocytosis to interact with histone proteins, then form nanoribbons of 67 inside nuclei of Saos2 cells. While this study further establish EISA forming intranuclear peptide assemblies, the detailed mechanism remains to be elucidated.…”
Section: Eisa Of Peptidesmentioning
confidence: 99%